2020
DOI: 10.3390/ijerph17082680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Sexual Function and Quality of Sexual Life Related to Menopausal Symptoms in Peri- and Postmenopausal Women: A Systematic Review

Abstract: During the menopausal period, sexual dysfunction is associated with the development or worsening of psychological conditions, causing deterioration in women’s mental health and quality of life. This systematic review aims to investigate the effects of different exercise programs on sexual function and quality of sexual life related to menopausal symptoms. With this purpose, a systematic literature search was conducted in PubMed, CINAHL, Scopus, Web of Science, and Cochrane Plus. A total of 1787 articles were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…The majority of previous systematic reviews focused on menopausal symptoms in terms of frequency and intensity [ 21 , 55 , 56 , 57 ]. A recently published meta-analysis only identified an association between physical exercise and quality of life related to menopausal sexual symptoms [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of previous systematic reviews focused on menopausal symptoms in terms of frequency and intensity [ 21 , 55 , 56 , 57 ]. A recently published meta-analysis only identified an association between physical exercise and quality of life related to menopausal sexual symptoms [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was substantial evidence showing the beneficial effects of exercise on oxytocin, cortisol, and estrogen levels, all of which are hormones that affect sexual function and orgasms. However, the association between exercise and sexual symptoms or QoL domains remains inconclusive [ 58 ]. Although regular exercise is theoretically believed to help improve menopausal symptoms and related QoL domains, current evidence of its beneficial effect is generally inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcelén-Fraile et al (2020) showed that resistance training, unlike aerobic exercise, did not affect female sexual function and quality of sexual life [ 22 ]. It is noteworthy that in previous studies, intervention was done more on the pelvic muscles [ 22 , 44 ] and less on the feet.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies on sexual function showed contradictory results of aerobic exercises and no effect of resistance training on patients' sexual functions [ 22 ]. The effect of reflexology was studied on factors such as the severity of fatigue [ 23 ], depression [ 24 ], restless legs syndrome [ 25 ], pain, muscle cramps [ 26 ], sleep quality [ 27 ] of the hemodialysis patients, but no study has investigated the effect of reflexology on sexual function of the hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%